Design of Highly Efficient Thermoelectric Materials Tailoring Reciprocal-Space Properties by Real-Space Modification - Zhu, Hao (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.